Iraq Crude Oil Exports – July, August, September, October, November, December/ 2023 - SOMO, Oil Marketing Company (Journal of Petroleum Research and Studies, 2024)
Table 1. Iraq Crude Oil Exports – July 2023 Table 2. Iraq Crude Oil Exports – August 2023 Table 3. Iraq Crude Oil Exports – September 2023 Table 4. Iraq Crude Oil Exports – October 2023 Table 5. Iraq Crude Oil Exports – November 2023 Table 6. Iraq Crude Oil Exports – December 2023